A linguagem de Role Playing Games Digitais e o ensino de inglês - Boscariol-Bertolino, Márcia Regina (2008)
The present interdisciplinary research is aimed at analyzing the most frequent verbs, its collocates and lexical patterns found in the texts of videogames, specifically the Digital Role Playing Games. It is proposed based in the results of the research, a material using the patterns for English Teaching using the patterns found in study corpus. There are many researches about characterization though there isn t any that make a description of the language of Digital RPGs following the theories of Corpus Linguistics and linked it to English teaching. The present aims fill in such gap. The research is based on the Corpus Linguistics theoretical frame. We use Task Based Learning how pedagogocal support. Two corpora were applied in this research : 1- the study corpus made of Digital RPGs texts with a total of about 600.000 words and the Contemporary Corpus of American English (COCA) with a total of 360 million tokens as the reference corpus used to help preparing the teaching materials. The research questions guiding the present study were: (1) what are the most frequent verbs found in the study corpus? (2) what are the typical lexicogrammar patterns found in the Digital RPG genre? (3) how is it possible to apply the patterns found in the texts to prepare task based activities? The results show many lexico-grammatical patterns that characterize the games and can be useful in English learning as foreign language, in Private and public schools, in different grade levels